2017
DOI: 10.18400/tekderg.307513
|View full text |Cite
|
Sign up to set email alerts
|

Toplu Ulaşımda Bekleme Süresini Etkileyen Faktörlerin İncelenmesi: Güvenilirlik, Yolcu Bilgilendirme Sistemi ve Fiziksel Koşullar

Abstract: Toplu ulaşımda bekleme süresi, yolcuların algıladığı hizmet seviyesinin en önemli boyutlarından biridir. Özellikle trafik koşullarının etkisi altında işletilen kent içi otobüs taşımacılığında aşırı bekleme süresi, yolcuların tür ve güzergâh seçimini değiştirebilecek bir fayda fonksiyonu bileşenine dönüşebilmektedir. Bu çalışmada, kent içi otobüs taşımacılığında karşılaşılan bekleme süresi, hat ve durağa ait fiziksel koşulların yanı sıra, güvenilirlik ve yolcu bilgilendirme sistemlerinin etkisi de dikkate alına… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
0
3
0
8
Order By: Relevance
“…On the other hand, the ANN, as a nonlinear approach, has high prediction capability, especially for private car choices. Doğan and Özuysal [13] have investigated the factors affecting waiting time in public transportation in terms of reliability, passenger information system, and physical condition. As the result of the constituted linear multiple regression models, they have found that passenger information system and reliability have reduced effect on waiting time by 2 and 1.3 minutes, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, the ANN, as a nonlinear approach, has high prediction capability, especially for private car choices. Doğan and Özuysal [13] have investigated the factors affecting waiting time in public transportation in terms of reliability, passenger information system, and physical condition. As the result of the constituted linear multiple regression models, they have found that passenger information system and reliability have reduced effect on waiting time by 2 and 1.3 minutes, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yapılan çalışmalar güvenilirliğin yolcuların tür ve güzergâh seçimleri üzerinde de etkili olduğunu ortaya koymuştur [2,3]. Ayrıca işletmecilerin güvenilirliği gözetici önlemler yerine daha yüksek hizmet düzeyi için sefer sıklığını arttırması halinde, işletmeciler açısından maliyet artışına ve filodan yararlanma oranının azalmasına yol açmaktadır [4].…”
Section: Introductionunclassified
“…However, considering the exact waiting time at the origin, a transfer point may provide more realistic results instead of considering it as half of the headway since the passengers have better knowledge owing to the intelligent transportation systems and mobile applications nowadays. Dogan andÖzuysal [25] state that excess waiting times in urban bus systems may lead to a change in transit users' route choice. Another widely accepted approach is the assumption of users' choice of routes with the shortest travel time.…”
Section: Introductionmentioning
confidence: 99%